Paradigma Perubahan Evolusi Pada Budaya Megalitik di Wilayah Budaya Nias - Ketut Wiradnyana (Kapata Arkeologi, 2015)
The culture area of Nias covers an island, which is Nias Island, and is divided into a number of culture sub-areas. Every culture sub-area consists of several villages, each with its distinct cultural elements. This discussion is aimed at understanding the differences of Nias culture from one village to the others, whether or not they are from one genealogy. The inter-village differences are not merely related to temporal aspect but also to cultural values, social structures and social functions. For that reason, description of cultural elements becomes the main phase, before they are interpreted. Depiction of differences of cultural elements from one village to the others, with structural and functional aspects as their background, will reflect the external and internal factors in an evolutionary cultural change. Therefore the inter-village cultural differences in Nias belong to a paradigm of evolutionary change like what was meant by Talcott Parsons.Wilayah budaya Nias itu meliputi satu pulau yaitu Pulau Nias. Di dalam wilayah budaya dimaksud terbagi atas subwilayah budaya. Pada sebuah subwilayah budaya, terdiri dari beberapa perkampungan, yang masing-masing  memiliki unsur-unsur budaya yang berbeda. Berkenaan dengan itu, tujuan pembahasan ini di antaranya adalah memahami perbedaan kebudayaan Nias antarperkampungan, baik di dalam satu genealogi ataupun tidak. Perbedaan antarkampung dimaksud tidak hanya berkaitan dengan aspek waktu tetapi juga, nilai budaya, faktor struktur sosial dan fungsi sosialnya. Berkenaan dengan itu maka uraian unsur kebudayaan menjadi tahapan utama, untuk selanjutnya diinterpretasikan. Gambaran perbedaan unsur kebudayaan antarkampung dengan aspek struktur dan fungsi yang melatarbelakanginya akan menggambarkan faktor eksternal dan internal pada sebuah perubahan evolusioner kebudayaan. Berkenaan dengan itu maka  perbedaan kebudayaan antarkampung di Nias merupakan  sebuah paradigma  perubahan evolusioner seperti apa yang dimaksud oleh Talcott Parsons.